Evaluation of Dental Anxiety in Parents Accompanying their Children for Dental Treatment (Orthodontic Journal of Nepal, 2013)
Objective: To evaluate the anxiety level of parents accompanying their children for the dental treatment. Materials & Method: Dental Anxiety Scale-Revised (DAS-R) questionnaire was filled by 101 subjects (53 females and 48 males) visiting the dental department for their children’s dental treatment. Result: 62.4 % parents accompanying their children had no or low anxiety levels and 9.9% and 5.9% showed high to severe anxiety levels respectively. There was no statistical significant difference seen between the anxiety levels in male and female parents. Conclusion: 37.6 % parents accompanying their children to the dentist showed moderate to severe anxiety levels with no significant difference seen in the overall anxiety levels of mothers and fathers. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9282 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 47-52